Застосування методів радіолокаційної інтерферометрії та георадарного знімання для моніторингу земель історико-культурного призначення - Четверіков, Б.; Chetverikov, B. (Видавництво Львівської політехніки, 2023)
Мета роботи – розглянути застосування геофізичних методів для локальних ділянок (супутникової радіолокаційної інтерферометрії та георадарного знімання) під час визначення меж земель історико-культурного призначення. Методика. Запропоновано комбінацію методик виявлення або уточнення меж об’єктів історикокультурної спадщини для встановлення охоронних зон. Ця комбінація поєднує два методи визначення або моніторингу земель історико-культурного призначення, а саме супутникову радіолокаційну інтерферометріюі наземне георадарне знімання. За допомогою супутникової радіолокаційної інтерферометрії визначають вертикальні зміщення земної поверхні, тобто просідання ґрунтів у місцях, де є можливі елементи об’єктів культурної спадщини (підземні ходи або підземні кімнати на території замкових комплексів, місця братських могил тощо). Після визначення місць найбільших вертикальних зміщень ґрунту ці ділянки досліджують георадаром на предмет виявлення аномалій, які згодом дешифрують. Поєднання цих методів дає змогу виявити додаткові елементи об’єктів історико-культурної спадщини, що містяться під землею, без археологічного втручання. Це дає можливість уточнити чинні межі земель історико-культурного призначення або виявити нові, що впливає на коригування охоронних зон. Результати. Результатом проведених досліджень є два приклади виявлення нових земель історико-культурного призначення за допомогоюкомбінації методів супутникової радіолокаційної інтерферометрії та георадарного у с. Нітішин і смт Брюховичі. На цих землях історико-культурного призначення є братські могили часів Другої світової війни, межі яких уточнено за допомогою зазначених методів, що слугує підставою для встановлення охоронних зон. Практична цінність. Результати застосування методів радіолокаційної інтерферометрії та георадарного знімання для дослідження об’єктів історико-культурного призначення можна використати для уточнення меж земельних ділянок відповідного фонду, щоб точніше скоригувати охоронні зони.

The purpose of the work is to consider the application of geophysical methods for local areas (satellite radar interferometry and ground-penetrating radar surveying) in determining the boundaries of lands of historical and cultural purpose. Method. A combination of methods for identifying or clarifying the boundaries of historical and cultural heritage objects for the establishment of protective zones is proposed. This combination includes two methods of determining or monitoring lands of historical and cultural purpose, namely satellite radar interferometry and ground-based GPR surveying. With the help of satellite radar interferometry, it is possible to determine vertical displacements of the earth’s surface, that is, subsidence of soils in places where there are possible elements of cultural heritage objects (underground passages or underground rooms on the territory of castle complexes, places of mass graves, etc.). After determining the locations of the largest vertical displacements of the soil, these areas are investigated by ground-penetrating radar for the detection of anomalies, which are subsequently deciphered. With the help of a combination of these methods, it is possible to identify additional elements of objects of historical and cultural heritage located underground without archaeological intervention. This allows clarifying the existing boundaries of lands of historical and cultural purpose or discovering new ones, which in turn affects the correction of protection zones. The results. As a result of the research, two examples of the discovery of new lands of historical and cultural purpose using a combination of satellite radar interferometry and georadar surveying in the village of Nitishyn and the village of Bryukhovychi are presented. These lands of historical and cultural purpose include mass graves from the time of the Second World War, the boundaries of which have been clarified using these methods, which serves as the basis for establishing protective zones. Practical value. The obtained results of the application of the methods of radar interferometry and ground-penetrating radar surveying in the study of objects of historical and cultural purpose can be used to clarify the boundaries of the land plots of the corresponding fund. It is more accurate to adjust the security zones according to the received border results.
Application of radar interferometry and georadar surveying methods for monitoring historical and cultural lands
Keywords: георадарні дослідження; радіолокаційна інтерферометрія; землі історико-культурного призначення; межі ділянок; ГІС; ground-penetrating radar research; radar interferometry; lands of historical and cultural purpose; site boundaries; GIS; 528.04